Evaluation of Asymptomatic Bacteriuria and Urinary Tract Infection in Patients With Primary Sjögren’s Syndrome - Zeynep ÇETİN,; Rıdvan MERCAN,; Ömer KARAŞAHİN,; Abdurrahman TUFAN,; Mehmet Akif ÖZTÜRK, (Archives of Rheumatology, 2020)
Objectives: This study aims to determine the frequency and risk factors of bacteriuria and urinary tract infection (UTI) in patients with primary Sjögren’s syndrome (SS) and their differences from healthy individuals and rheumatoid arthritis (RA) patients. Patients and methods: The study included 107 female primary SS patients (mean age 50.7±11.6 years; range, 23 to 76 years), 53 healthy female control subjects (mean age 46.8±15.5 years; range 21 to 80 years), and 40 females with RA (mean age 51.7±14.2 years; range, 25 to 79 years). Participants were questioned for UTI risk factors and symptoms. Middle stream urine samples were taken and cultured. All participants were examined with urinary symptom questioning survey of American Urological Association (AUA-7). Results: The urine cultures were positive in 18 primary SS patients (16.8%), eight RA patients (20%), and two healthy controls (3.7%). Escherichia coli, enterococci, Klebsiella, streptococci, and candida were detected in SS patients’ cultures. Extended-spectrum beta-lactamase was positive in three cultures. Asymptomatic bacteriuria was not detected in any SS patient. The highest AUA-7 score was determined in SS group (p=0.031). Nineteen SS patients had vaginal dryness symptom and their AUA-7 scores were higher than the rest of the SS group. The risk of UTI development was not different between those who had or did not have vaginal dryness. Conclusion: Urinary tract infections are seen more often in SS patients rather than normal population, which may be caused by SS’ urinary system effects. It is difficult to distinguish between asymptomatic bacteriuria and infection because of the underlying urinary symptoms. Clinicians must be careful in patients receiving immunosuppressive therapy due to the high frequency of UTIs.